2010
DOI: 10.1111/j.1365-2605.2009.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal dysfunction in male cancer patients before cytotoxic treatment

Abstract: Male patients diagnosed with cancer are often referred for semen cryopreservation before gonadotoxic treatment but often have low semen quality. The aim of this study was to evaluate which type of cancer affects gonadal function and proposes a risk factor for low pre-treatment semen quality. Between January 1983 and August 2006, 764 male cancer patients were referred for semen cryopreservation prior to chemotherapy and radiotherapy. We compared semen characteristics and reproductive hormones between different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 13 publications
6
53
0
Order By: Relevance
“…Whereas several studies have shown that malignancies, especially testicular cancer and lymphoma, in male patients adversely affect fertility before the initiation of the oncologic treatment [9], in women data are conflicting. An adverse influence of malignancy on oocyte biology was first reported by Pal et al [10].…”
Section: Introductionmentioning
confidence: 90%
“…Whereas several studies have shown that malignancies, especially testicular cancer and lymphoma, in male patients adversely affect fertility before the initiation of the oncologic treatment [9], in women data are conflicting. An adverse influence of malignancy on oocyte biology was first reported by Pal et al [10].…”
Section: Introductionmentioning
confidence: 90%
“…Interest in the effect of cancer on ovarian function has probably been fueled by reports of decreased sperm quality and count in patients with cancer 4,5 . Those observations sparked an interest in reports describing baseline ovarian function and outcomes of ovarian stimulation in patients needing fertility preservation because of background malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrated a negative effect of cancer on spermatogenesis, with a decrease in sperm quality and indices in patients diagnosed with hematologic and testicular cancers 4,5 . Likewise, the effect of cancer on baseline ovarian function and ovarian response to stimulation for in vitro fertilization (ivf) has been studied with mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Women diagnosed with cancer have different options for fertility preservation, but embryo freezing after in vitro fertilization (IVF) seems the best option available today. Concerns over ovarian response in cancer patients during IVF treatment are now being brought up in conjunction with studies of men with cancer who demonstrate reductions in sperm count and quality even before treatment (1,2). However, the data regarding this subject with women are conflicting.…”
mentioning
confidence: 94%